Concomitant Use of Analgesics and EGFR TKIs in Lung Cancer Patients: Outcomes and Perspectives From a Finnish Retrospective Register–Based Study - Laura S. Puuniemi; Sanna M. E. Iivanainen; Martti Arffman; Riitta L. Kaarteenaho; Jussi P. Koivunen (Cancer Medicine)
ABSTRACT Introduction Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are used in the treatment of non‐small cell lung cancer (NSCLC). Preclinical studies suggest inflammatory and other mechanisms of analgesics affect the efficacy of EGFR TKIs. In this study, we aim to explore the outcomes of concurrent use of EGFR TKIs and analgesics, to provide clinical insight into analgesic treatment decisions. Methods Patients (n = 1494) with EGFR TKI reimbursements (2011–2020) and data available in the Finnish Cancer Registry with concurrent analgesics purchases (nonsteroidal anti‐inflammatory drugs [NSAID], acetaminophen, weak and strong opioids, strong opioids stratified by immunomodulatory properties) were identified. Overall survival (OS) and time‐on‐treatment (ToT) were analyzed using univariate and multivariate Cox models and Kaplan–Meier. Results In multivariate analysis for ToT, weak and strong opioids were associated with inferior outcomes (HR 1.368, 95% CI 1.119–1.674, HR 1.454, 95% CI 1.276–1.656) compared to no analgesics, while NSAID and acetaminophen showed no association. Multivariate analysis for OS showed inferior survival among EGFR TKI‐treated patients with weak (HR 1.290, 95% CI 1.043–1.595) and strong opioid (HR 1.690, 95% CI 1.471–1.940) purchases, while this was not seen with NSAID. Compared to nonimmunomodulatory opioids, patients with immunomodulatory opioid purchases had unfavorable outcomes for both ToT (HR 1.448, 95% CI 1.148–1.826) and OS (HR 1.479, 95% CI 1.158–1.888). Conclusions In EGFR TKI‐treated NSCLC, opioids are an independent risk factor for worse ToT and OS. The outcomes differed by immunomodulatory category of opioids, suggesting analgesics class can potentially have an impact on EGFR TKI effects.